IL-6 Receptor Inhibition by Tocilizumab Attenuated Expression of C5a Receptor 1 and 2 in Non-ST-Elevation Myocardial Infarction - Orrem, Hilde L.; Nilsson, Per H.; Pischke, Søren E.; Kleveland, Ola; Yndestad, Arne; Ekholt, Karin; Damås, Jan K.; Espevik, Terje; Bendz, Bjørn; Halvorsen, Bente; Gregersen, Ida; Wiseth, Rune; et al. (Frontiers in Immunology, 2018)
Abstract Background. Elevated interleukin-6 (IL-6) and complement activation are associated with detrimental effects of inflammation in coronary artery disease (CAD). The complement anaphylatoxins C5a and C3a interact with their receptors; the highly inflammatory C5aR1, and the C5aR2 and C3aR. We evaluated the effect of the IL-6 receptor (IL-6R)-antagonist tocilizumab on the expression of the anaphylatoxin receptors in whole blood from non-ST-elevation myocardial infarction (NSTEMI) patients. Separately, anaphylatoxin receptor expression in peripheral blood mononuclear cells (PBMC) from patients with different entities of CAD was investigated. Materials and methods. NSTEMI patients were randomized to one dose of tocilizumab (n=28) or placebo (n=32) and observed for 6 months. Blood samples drawn at inclusion, at day 2, 3 and after 6 months were analyzed. Patients with different CAD entities comprised stable angina pectoris (SAP, n=22), non-ST-elevation acute coronary syndrome (NSTE-ACS, n=21) and ST-elevation myocardial infarction (STEMI, n=20) were examined at hospital admission. mRNA was isolated from whole blood and PBMC. Anaphylatoxin-receptor-expression was analyzed with qPCR. Complement activation was measured as plasma sC5b-9 by ELISA. Results. Our main findings were (i) Tocilizumab decreased C5aR1 and C5aR2 mRNA expression significantly (p<0.001) and substantially (>50%) at day 2 and 3, whereas C3aR expression was unaffected. (ii) Tocilizumab did not affect complement activation. (iii) In analyzes of different CAD entities C5aR1 expression was significantly increased in all CAD subgroups compared to controls with the highest level in the STEMI patients (p<0.001). For C5aR2 and C3aR the expression compared to controls were very modest, though still significant, for C5aR2 in the STEMI group (p<0.05) and C3aR in the NSTE-ACS group (p<0.05). Conclusion. Expression of C5aR1 and C5aR2 in whole blood was significantly attenuated by IL-6R-inhibition in NSTEMI patients. These receptors were significantly upregulated in PBMC CAD patients with particularly high levels of C5aR1 in STEMI patients.